Device for automatic accuracy control of dial indicator readings - Samborski, Tomasz; Zbrowski, Andrzej; Kozioł, Stanisław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2025)
The authors present a research method and a prototype of a system for automatic accuracy control of manual measuring instrument readings. Most commonly used measuring instruments, such as dial indicators and bore gauges, require periodic accuracy control. The developed system is intended for control automation, minimising potential human errors connected with manual control and visual assessment of readings. The precise mechatronic actuators, measurement systems, and control software used in the system enable automatic execution of standard control procedures in accordance with the formal recommendations of the Central Office of Measures. The scientific and research results obtained will serve the development of methods for processing and analysing measurement data.